Analisis Pemilihan Moda Transportasi Mahasiswa Universitas Tangerang Raya Menggunakan Metode Analytical Hierarchy Process (AHP) Dan Regresi Logistik Biner - Rico Aris Sunaryo; Raka Surya Pradana; Siska Dewi (Science and Education Journal (SICEDU), 2026)
Transportation mode choice is an essential aspect of transportation planning because it reflectstravelers' behavior and travel characteristics. This study aims to analyze the travel characteristics ofstudents at Universitas Tangerang Raya, identify the priority factors influencing transportation modechoice using the Analytical Hierarchy Process (AHP), and examine the effects of these factorsthrough Binary Logistic Regression. A quantitative approach was employed by distributingquestionnaires to 98 active students selected using the Slovin sampling formula from a population of4,157 students. The collected data were analyzed using Microsoft Excel for the AHP method andIBM SPSS Statistics for Binary Logistic Regression analysis. The results indicate that motorcyclesare the most frequently used mode of transportation, accounting for 72.45% of students' travelchoices. The AHP analysis reveals that transportation mode availability is the most influential factor,with a priority weight of 19.42%, followed by safety (19.12%), accessibility (17.24%), comfort(16.18%), travel speed (14.39%), and travel cost (13.65%). Furthermore, the Binary LogisticRegression analysis demonstrates that safety considerations, vehicle ownership, and transportationexpenditure significantly influence students' transportation mode choice. These findings providevaluable insights for Universitas Tangerang Raya and related stakeholders in formulating effective,safe, and sustainable campus transportation policies.